Social Demand and the Supply of University Education in Nigeria, 1980-2005 - Satope, Bola Funmilayo (2015)
The study examined the validity of the Fields' proposition that continuous expansion of universities in Nigeria might be due to political response to social demand. It also analysed the trend and pattern of university education between 1980 and 2005 and examined the influence of higher education policy on university expansion. This was with a view to determining the factors responsible for the rapid expansion in university education in the last two and a half decades.